PENERAPAN PEMBELAJARAN CLIS PADA MATERISSIFAT-SIFAT CAHAYA UNTUK MENINGKATKANSHASIL BELAJAR SISWA KELASSV - Ardiana, Nana; Jayadinata, Asep Kurnia; Gusrayani, Diah (Jurnal Pena Ilmiah, 2017)
This study was conducted by low level of student understanding of the five grade towards the material properties of light that caused low student learning outcomes. The main factor is teacher centered learning. To solve this problem, the writer designed a lesson plan by applying Children Learning in Science (CLIS). The CLIS learning model is student centered where the students are actively involved in the learning process through hands-on/minds on activities. This research is a classroom action research using Kemmis and Taggart design. There was an increase in each cycle, the cycle I students complete 19 people or 51.4%, the cycle II students complete 30 people or 81.1%, and the cycle III as many as 36 students or 97.3%. Thus, through the application of CLIS learning model can improve students’ learning outcomes of five grade on the material properties of light.